Allergic Rhinitis as an Independent Risk Factor for Postoperative Recurrence of Children Chronic Sinusitis - Caixia Zhang; Hua Zhang; Qingping Tang; Junyi Zhang; Shuo Wang; Zhihai Xie; Weihong Jiang (MDPI AG, 2023)
(1) Background: The recurrence rate of childhood recurrent sinusitis varies widely between 12% and 50%, with the postoperative recurrence risk factors remaining largely unidentified. We sought to enhance the understanding of chronic rhinosinusitis (CRS) via a retrospective observational childhood cohort. (2) Methods: The study recruited 125 cases. Demographic data and univariate and multivariate logistic regression analyses were conducted to investigate potential risk factors of childhood recurrent sinusitis following functional endoscopic sinus surgery (FESS). (3) Results: A postoperative recurrence rate of 21.6% was determined. Among the participants, 21 cases presented a history of allergic rhinitis (AR), with the remaining 104 cases being AR-free. A significantly heightened recurrence rate was noted in those bearing a history of AR compared to their counterparts devoid of such history (p < 0.000). The fully adjusted logistic regression model indicated a 21.04-fold increased risk of postoperative recurrence in childhood CRS bearing a history of AR compared to those without an AR history (p = 0.000), highlighting the history of AR as an independent risk factor for postoperative childhood recurrent sinusitis (p = 0.001); (4) Conclusions: The data implicate AR as an independent risk factor for postoperative childhood recurrent sinusitis.